Relationship between PLKN programme and entrepreneurial personality among youths in Malaysia - Chee, Hee Hoe; Abdullah, Haim Hilman; Md Isa, Filzah; Jaganathan, Mathivannan; Mohd Yunus, Jasmani (2014)
The main objective of this study is to examine the influence of the National Service Training Programme modules of physical training, nation building, character building and community service on entrepreneurial personality of the trainees. The study was conducted on a sample size of 345 students of Universiti Utara Malaysia who had undergone these four important modules of the National Service Training Programme.The findings revealed that there is a positive relationship between modules of the National Service Training Program and entrepreneurial personality among youths.This relationship can be attributed to increasing demands from youths to seek for quality education from educational institutions that could equip them with the entrepreneurial competencies in preparing them for future careers.Moreover, the National Service Training Program is an ideal platform considered for introducing and inculcating the entrepreneurial culture among youths while they are under going national service.Hence, this paper posits that it is important for the government to provide entrepreneurial friendly environment in their bid to encourage and foster the entrepreneurial culture amongst the youths in Malaysia.